A study on occurrence of anemia in primigravida women attending antenatal ward of BPKIHS - Yadav, Upendra; Das, B Lal (Health Renaissance, 2017)
Background: Anemia is identified as a very common nutritional problem in developing countries. Prevalence of micro nutrient malnutrition in respect of iron, iodine and vitamin A is more wide spread then protein energy malnutrition. Pregnancy is a serious burden to the women with the disease for the anemia and places them at increased risk of mortality. Objective: To determine the Hb% level of Primigravida women. To classify status of anemia on the basis of level of Hb%. To find out the association between Hb level and selected background factors. To find out the association between the Hb% level and week of gestation and nutritional pattern. Method: A descriptive and exploring Study design was carried out on 300 primigravid women admitted in BPKIHS, Dharan antenatal ward and every alternate admitted case was selected for the study. The instrument was structured questionnaires with close ended, observation check list and observational sheet. Descriptive statistics and inferential statistics were used for data analysis. Result: Overall occurrence of anemia was found to be 42% among the study population. Mild anemia and moderate anemia were found to be 17% and 25% respectively. Greater proportions of 13-19 yr. women were found to be anemic compares to those > 20 years of age. Greater proportions of anemic women were from the nonsedentary groups than the sedentary. Both mild and moderate anemia were more among Primigravid women with >40 gestational week. Conclusion: Understanding the extent and severity of anemia among pregnant women is essential to the development and implementation of effective anemia control for the normal delivery and healthy baby in Nepal. Health Renaissance 2015;13 (3):